Reducing the Vulnerability of Albania's Agricultural Systems to Climate Change : Impact Assessment and Adaptation Options - Sutton, William R.; Srivastava, Jitendra P.; Neumann, James E.; Strzępek, Kenneth M.; Droogers, Peter (Washington, DC: World Bank, 2013)
Changes in climate and their impact on agricultural systems and rural economies are already evident throughout Europe and Central Asia (ECA). Adaptation measures now in use in Albania, largely piecemeal efforts, will be insufficient to prevent impacts on agricultural production over the coming decades. There is growing interest at the country and development partner levels to have a better understanding of the exposure, sensitivities, and impacts of climate change at farm level, and to develop and prioritize adaptation measures to mitigate the adverse consequences. Specifically, this report provides a menu of climate change adaptation options for the agriculture and water resources sectors, along with specific adaptation actions, that are tailored to four distinct agro-ecological zones (AEZs) within Albania. This menu reflects the results of three inter-related activities, conducted jointly by the team and local partners: (1) quantitative economic modeling of baseline conditions and the effects of climate change and an array of adaptation options; (2) qualitative analysis conducted by the team of agronomists, crop modelers, and water resources experts; and (3) input from a series of participatory workshops for national decision makers and farmers in each of the AEZs. This report provides a summary of the methods, data, results, and adaptation options for each of these activities.